(untitled) (International Journal of Current Engineering and Technology, 2015)
Stationary gas turbines are preferred over other prime movers for power generation due to its low specific fuel consumption. The gas turbine power plants and steam turbine bottoming cycle are used as co-generation technique for improving overall efficiency of the plant. The utilization of fuel and its effective combustion derives the primary cycle efficiency. Hence combustion chamber of gas turbine should provide necessary chemical kinetics and species generation with effective cooling of flame tube. In the present paper the need for assessment of process design parameters of gas turbine combustion chamber is addressed. Design procedure and dimensions of combustion chamber of gas turbine working on producer gas is presented.